Word-formation in European languages. (November 2018) - Körtvélyessy, Lívia; Štekauer, Pavol; Genči, Ján; Zimmermann, Július
Abstract : The main goal of the paper is to analyze and evaluate the nature and the role of word-formation systems in a sample of 73 European languages. The basis for the comparison is 100 word-formation features representing 12 word-formation processes. The data is used to examine (a) the structural richness of word-formation systems at the level of individual languages, language genera, families and the linguistic area of Europe, and (b) the parameter of Maximum Feature Occurrence that identifies those word-formation features that are present in all languages under consideration, i.e., in all languages of a genus, a family or a linguistic area of Europe. In the latter case, it identifies the so-called Euroversals. From the diachronic perspective, the paper evaluates the degree of diversification of languages belonging to the same language genus and language family.